Some Useful Applications Of Mathematics And Statistics In Economics - Pant, Seema; Nehra, Ankur (International Journal of Psychosocial Rehabilitation, 2024)
The purpose of this research is to investigate how statistics and mathematics are used in economics. It will look at how these quantitative techniques are used to evaluate economic information and come to wise conclusions. The advantages and restrictions of using statistics and mathematics in economics will also be examined in this study. According to Weintraub's research, economics does not have a fixed point of reference in mathematics. He describes how the ideas of consistency and rigor in mathematics have evolved and how it has shown to be impossible to represent mathematics as a fully formed formal system. This makes it easier to recognize how applied economics, which prioritizes quantitative language, has methodological ambiguities. This paper's goal is to examine fundamental mathematical tools that are frequently employed in the study of economics, including microeconomics, macroeconomics, and econometrics. Without the application of mathematics, economic ideas are insufficient. Each topic in economics requires the application of mathematics for a correct understanding. Economic topics are made understandable by the application of mathematical tools, which might pique one's interest in the subject.